The Influence of the Existence of Zoning Schools on Equality of Access to Education in Malang Regency - Dipo Piswatama; Tiur Malasari Siregar (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2025)
This research examines the influence of the existence of zoned schools on equal access to education in Malang district. The problems in this research are the pros and cons of school principals, teachers, parents and students regarding the school zoning system in Malang district. Based on research conducted by researchers, many school principals, teachers, parents and students do not agree with the existence of a school zoning system. Because students who excel and are competent do not get favorite schools to support their long-term careers. On the other hand, from the teacher side, teachers are very depressed and stressed because they find so few talented and high-quality students in the learning process at school. This research uses qualitative methods in the form of interviews with school principals, teachers, parents and students in the school environment. The research results prove that in the absence of an educational zoning system in Indonesia, you will find many students who excel and excel in elementary, middle and high school. Because with the student zoning system there tends to be no competition between students and other students. However, this has led to a decline in the quality of education in Indonesia through the school zoning system.